Efficacy of organic acid salts in improving soybean meal as fishmeal replacement in the diet of blue swimming crab, Portunus pelagicus (Linnaeus, 1758) juveniles - Mohd Taher, Nur Ain Sofea (2021)
Due to the ever-rising cost of commercial feeds for aquaculture species, it is becoming increasingly necessary to find new ingredients that are economically viable, do not harm the environment, and can meet the metabolic needs of blue swimming crab juveniles. A series of experiments was conducted to determine the optimum level of soybean meal as a fishmeal replacement in the diet on blue swimming crab juveniles and the use of organic acid salts to enhance soybean utilization of the crabs. The organic acid salts were then tested against Vibrio harveyi to determine whether they could inhibit the pathogenic bacteria. The crabs were housed individually in separate containers and were fed with their respective experimental diets for four weeks. Crabs were fed with six experimental diets containing different levels of fishmeal replacement with soybean meal (0, 20, 40, 60, 80 and 100%). The crabs fed 20% soybean meal diet had the best performance for growth, feed utilization, body proximate composition, nutrient retention, and histopathology of hepatopancreas. Based on this finding, subsequent feeding trials were conducted in which sodium acetate was supplemented in the diets to determine if it could improve the utilization of 20% soybean meal. Five different concentrations of sodium acetate (0, 1, 2, 3 and 4%) tested. It was found that 2% sodium acetate resulted in improved survival, growth performance, feed utilization, lipid and protein composition of body tissue, and hepatopancreatic tubule structure. Concentrations lower or higher than 2% reduced the growth performance of the crabs. The optimal level of 2% was then used for the next feeding experiment with six different types of organic acid salts supplemented into the diets, including no organic acid salt, sodium acetate, sodium butyrate, sodium citrate, sodium formate and sodium propionate. This study was designed to determine the best type of organic acid salts that could enhance soybean meal utilization, which could lead to the most optimum growth performance of the crabs. The crabs fed sodium acetate had the best growth performance compared to those fed with other organic acid salts, which implied that the optimum concentration with the correct type of organic acid salts played a crucial role in the growth of aquaculture species. A total of 30 crabs from each treatment were then used in a follow-up investigation to test if the organic acid salts could inhibit V. harveyi at a concentration of 107 CFU mL-1. LC50 was first conducted to determine the lethal concentration of the V. harveyi to be used in the challenge test. The results showed that crabs fed dietary sodium acetate were able to resist pathogenic bacteria better than those fed other treatments, as evidenced by higher survival (83.33%), lower Vibrio count in the hepatopancreas (5.18 ± 0.06 CFU mL-1) and culture water (1.38 ± 0.01 CFU mL-1) and improved hepatopancreas and gill structure after a 7-day of bacterial challenge. This study found that 20% of fishmeal replacement with soybean meal was recommended for blue swimming crab juveniles and 2% sodium acetate was the best concentration and type of organic acid salts for enhancing the soybean meal utilization by the crabs. The potential of sodium acetate to inhibit V. harveyi has been demonstrated.